Peran Pokdarwis Argowayang sebagai Ruang Belajar untuk Memberdayakan Masyarakat Desa Galengdowo - Farid, Muhammad; Nusantara, Widya (J+PLUS UNESA, 2023)
The goal of this research is to describe, (1) the role of the pokdarwis Argowayang as a community learning space, and (2) the purpose of the learning space in the pokdarwis Argowayang is to form awareness in the Galengdowo village community through socialization and education as a form of community empowerment. This research method is descriptive qualitative. To obtain data regarding learning spaces and community empowerment in the Argowayang pokdarwis, researchers collected data using participatory observation, interviews, and documentation techniques. The results of this research show that Pokdarwis Argowayang have a role as an organization that accommodates the learning process and empowers the community through socialization and discussion to form knowledge, skills and community awareness in realizing the elements of Sapta Pesona in Galengdowo village to make Galengdowo village a tourist village. Thus, it can be concluded that Pokdarwis Argowayang can be used as a learning space for community empowerment which is able to increase community awareness and mobilize the community actively and participatively in the development of the tourism sector as a form of community empowerment.